2017
DOI: 10.1108/imds-08-2016-0333
|View full text |Cite
|
Sign up to set email alerts
|

Modeling errors in parts supply processes for assembly lines feeding

Abstract: Purpose The purpose of this paper is to develop a quantitative model to assess probability of errors and errors correction costs in parts feeding systems for assembly lines. Design/methodology/approach Event trees are adopted to model errors in the picking-handling-delivery-utilization of materials containers from the warehouse to assembly stations. Error probabilities and quality costs functions are developed to compare alternative feeding policies including kitting, line stocking and just-in-time delivery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…This is because the operator is relieved of activities associated with sorting components into kits. Furthermore, cobotsupported sorting can remove the risk of human errors with respect to misplacing components between kits, which is important when kitting is used in industry [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the operator is relieved of activities associated with sorting components into kits. Furthermore, cobotsupported sorting can remove the risk of human errors with respect to misplacing components between kits, which is important when kitting is used in industry [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…With kitting, the process by which kits are preparedthe kit preparationis typically reported as labour-intensive, and time efficiency is key for keeping running costs low [4]. Moreover, manual kit prepara-tion is prone to human errors that lead to errors in kits, which are disruptive and costly at assembly processes [5,6]. Recent research has shown that robots can support time-efficient kit preparation by relieving pickers of some of the tasks in kit preparation while simultaneously supporting kit quality by removing the risk of human errors [7][8][9].…”
Section: Introduction and Aim Of The Studymentioning
confidence: 99%
“…In two recent studies, Caputo, Pelagagge, and Salini (2017a) and Caputo, Pelagagge, and Salini (2017b) developed comprehensive models for estimating the costs of kit errors in kit preparation. They defined five error types: missing component, wrong component, damaged component, wrong number of components, and wrong component position, and developed event trees for estimating quality-related costs based on how severe the error types were for the assembly process.…”
Section: Previous Research Dealing With Quality In Kitting and Warehomentioning
confidence: 99%
“…An example is to improve response time for supplying the right component by using a location closer to the assembly process, as identified by Hanson, Johansson, and Medbo (2011). Such links can help address the propagating errors in the model by Battini et al (2015), and the severity of various error types in Caputo, Pelagagge, and Salini (2017a) and Caputo, Pelagagge, and Salini (2017b).…”
Section: Framework For Analysing Links Between Kit Errors and Kit Prementioning
confidence: 99%
See 1 more Smart Citation